Driving mechanism of farmers' green production behavior under normalization of COVID-19 prevention and control: A case study in China - Teng, Yun; Pang, Boyuan; Zhang, Mei; Guo, Xiangyu (Frontiers in Public Health, 2022)
China's public health emergency COVID-19 has brought great challenges to food safety. Among them, the quality and safety of agricultural products under the normalization of the COVID-19 prevention and control has become a hot issue of general concern. This study attempts to reveal the driving factors and mechanisms of farmers' green production behavior. The empirical research by collecting 673 sample data shows that: individual characteristics of farmers, government guiding factors, an industrial organization promoting factors, and market adjustment factors have a positive driving effect on farmers' green production behavior. And farmers' green production behavior has a positive influence on the quality and safety of agricultural products. Farmers' green production behavior plays an intermediary role between the quality and safety of agricultural products and individual characteristics of farmers, government guidance factors, industrial organization promotion factors, and market regulation factors. The results of the study have guiding significance for ensuring the quality and safety of agricultural products, promoting ecological environmental protection, and sustainable agricultural development under the normalization of COVID-19 prevention and control.